Analisa Perbandingan Model PJBL Dengan Model TCL Menggunakan PLC ZELIO pada Instalasi Motor Listrik Kelas XII di SMK VOCTECH 1 Kota Tangerang - Anna Safitri; Didik Aribowo; Mohammad Fatkhurrokhman (STAI Miftahul Ula Nganjuk, 2020)
The success of learning requires the components that support it, one of which is a learning model. The right learning Model can help students easily understand learning materials. Research focus on learning differences in student outcomes from the use of two learning models, namely Project Based Learning (PJBL) and conventional models (lectures), and calculates the effectiveness of the PJBL model using PLC Learning Media in the electricity engineering program at SMK Voctech 1 Tangerang City. The research Model used in this study is quantitative with a pseudo-experimental research method with the type of Nonequivalent control group design. This research consists of several stages, namely the preparation stage, then the implementation stage of the research, and the completion stage of the research. The data analysis used in this research is Test U and test-T. Based on the research done, the results are: (1) There are different learning outcomes on TCL and PJBL, in the realm of cognitive u = 21,000 and significance 0.000. In the realm of psychomotor t = 11,802 and significance 0.000. (2) The effectiveness of the PJBL model in the cognitive realm with the average value of the student score is 0.6183 which belongs to the category